The Relationship Between Frequency of Infant Massage and Spa with The Quality of Sleep among Infants Aged 3-6 Months at The City Health Center - Padeng, Eufrasia Prinata; Laput, Dionesia Octaviani; Halu, Silfia Angela Norce; Nanur, Fransiska Nova; Dewi, Imelda Rosniyati; Bandur, Paskalinda Maria Yosefa; Raden, Natalia Damaiyanti Putri (Universitas Tribhuwana Tunggadewi, 2024)
The quality of infant rest can be defined as a specific physiological state occurring when the child is at rest. Infants who receive adequate rest without frequent waking tend to be healthier and less irritable the next day. The quality of infant rest can be assessed by the duration of rest and any discomfort experienced during or after rest. According to WHO data from 2012, approximately 33% of infants experience sleep problems. This study aimed to investigate the effect of baby massage and spa frequency on sleep quality in infants aged 3-6 months. Using a quantitative approach, the study sampled 40 mothers and their infants at the City Health Center. The results showed a correlation between baby spa frequency and sleep quality. The study recommends conducting baby spa training and suggests future research explore the combination of massage with other interventions like music or aromatherapy to enhance sleep quality. This research aims to provide insights into the benefits of baby spa and massage for infant sleep quality and to recommend these interventions as part of routine care programs in health facilities